BENTUK DAN FUNGSI PERTUNJUKAN TARI KUDA LUMPING “MASAL DEWASA” : STUDI ETNOKOREOLOGI DI PAGUYUBAN TURONGGO BUDHOYO MASIRAN - Yunanto, Nur Yasin; Kususmastuti, Eny (Institut Seni Indonesia Surakarta, 2025)
This study investigates the form and function of the “Masal Dewasa” Kuda Lumping dance as performed by the Turonggo Budhoyo community in Masiran Hamlet, Kaligading Village, Boja District, Kendal Regency. It addresses two research questions: (1) What constitutes the form of the “Masal Dewasa” Kuda Lumping dance? and (2) What functions does this performance serve? Framed by M. Jazuli’s theoretical perspective, the study employs a qualitative methodology with a descriptive ethnochoreological approach. Data were gathered through participant observation, in‑depth interviews, and performance documentation. Findings indicate that the “Masal Dewasa” Kuda Lumping dance is a collective ensemble performance comprising ten interrelated elements—among them theme, movement vocabulary, performers, musical accompaniment, props, costumes, make‑up, and floor patterns. Functionally, the dance fulfills ceremonial, entertainment, spectacular, social, and cultural‑preservation roles. In this way, it operates not only as an artistic expression but also as a living symbol of the local community’s cultural identity.